Cellular migratory aspects in the lungs of naïve and BCG immunized mice infected with Mycobacterium tuberculosis - Kipnis, Andre, author; Orme, Ian M., advisor; Basaraba, Randall J., committee member; DeMartini, James C., committee member; Fox, Michael M., committee member; Turner, Joanne, committee member (Colorado State University. Libraries, 2004)
Granuloma is the hallmark lesion formed in pulmonary tuberculosis and it is important for both the protective immunological response as well as the development of chronic disease. In this study, I evaluated different aspects of the immune response thought to be important in the trafficking of leukocytes during Mycobacterium tuberculosis infection in mice. In order to understand the role of some chemokines and adhesion molecules in pulmonary tuberculosis in mice, I describe in Chapter 2 the role of Chemokine Ligand 2 (CCL2, Monocyte Chemoattractant Protein-1) and in Chapter 3 the role of the adhesion molecule CD44. CCL2 is thought to be primarily responsible for recruiting monocytes, dendritic, NK and activated T cells, all of which have critical roles in the effective control of tuberculosis infection in mice. I show here that in mice in which the CCL2 gene was disrupted, animals exposed to low dose aerosol infection with Mycobacterium tuberculosis had fewer macrophages entering the lungs but only exhibited a minor and transient increase in bacterial load in the lungs, and were still able to establish a state of chronic disease. Such animals showed similar numbers of activated T cells as determined by their expression of the CD44hiCD62Llo phenotype, but a transient reduction in cells secreting IFN-γ indicated that the primary deficiency in mice unable to produce CCL2 is a transient failure to focus antigen-specific T lymphocytes into the infected lung, whereas other elements of the acquired host response are compensated by other ligands interacting with chemokine receptor CCR2. Upregulation of expression of the cell surface marker CD44 is a major characteristic of T lymphocytes responding in the lungs of mice infected with Mycobacterium tuberculosis. These lymphocytes express an activated/memory phenotype as seen by their high expression of the CD44 molecule and low expression of CD62L and CD45RB cell surface molecules. Based on increasing evidence that the CD44 molecule participates in several aspects of the inflammatory response, I evaluated its role in the response to infection with M. tuberculosis using gene-disrupted mice. I show that CD44 expression is not necessary for the proper trafficking of protective cells to the lungs of mice infected with M. tuberculosis, or the direct expression of protective immunity leading to control and containment of the bacterial load in this organ. However, although there were no differences in the bacterial load or migration of activated T lymphocytes to the inflamed lung, the absence of the CD44 molecule resulted in a substantially increased accumulation of neutrophils in the lung. These data indicate that loss of CD44 expression does not alter expression of TH1 immunity to tuberculosis in the lungs, but has major effects on the overall cellular composition of the immunopathological response. Finally, in Chapter four I approached cellular trafficking into the lungs when a memory adaptive response is generated by vaccinating mice with M. bovis BCG. I investigated the cellular response in the lungs to an aerosol infection with Mycobacterium tuberculosis, comparing BCG immunized and non-immunized control mice. Following exposure to pathogenic bacteria, immunized mice showed a significant increase in T cell influx in the lungs as early as 10 days post challenge, while non-vaccinated mice showed a significant T cell influx only at 20 days post challenge. As a consequence of this early cellular recruitment to the lungs, immunized mice could control the bacterial load in the lungs at ten times lower levels than control mice. Further investigation of vaccinated mice prior to M. tuberculosis challenge provided evidence that T lymphocytes with an effector/activated phenotype are present in the lungs of those mice at higher numbers as compared to control mice. There was also a significantly higher level of T cells that responded to stimulatory antibodies by producing IFN-γ. The presence of elevated numbers of T lymphocytes in the lungs of immunized mice allowed the host to respond sooner to an aerosol infection and maintain the pathologic response to infection in a reduced state as compared to control mice. Analyses of mRNA levels for IFN-γ in the lungs of BCG immunized mice showed that they are as low as mRNA levels from naive mice. Taken together, the data suggest that BCG immunized mice have increased number of T cells capable of producing IFN-γ but that are not doing so. Thus the T cells present in the lungs of immunized mice fit the category of memory effector phenotype and are important for the early control of the pulmonary tuberculosis infection.
Keywords: immunology; microbiology; pathology